Utilizing Multilingual Methods and Rapid Analysis for Global Qualitative Research During a Pandemic. (11th February 2022) - Graetz, Dylan E.; Sniderman, Elizabeth; Villegas, Cesar; Ragab, Iman; Laptsevich, Aliaksandra; Maliti, Biemba; Naidu, Gita; Zhang, Hui; Gassant, Pascale; Nunes, Luciana; Arce, Daniela; Vasquez, Jacqueline Montoya; et al.
Historically, qualitative research has complemented quantitative biologic and epidemiologic studies to provide a more complete understanding of pandemics. The COVID-19 pandemic has generated unique and novel challenges for qualitative researchers, who have embraced creative solutions including virtual focus groups and rapid analyses to continue their work. We present our experience conducting a multilingual global qualitative study of healthcare resilience among teams of pediatric oncology professionals during the COVID-19 pandemic. We provide an in-depth description of our methodology and an analysis of factors we believe contributed to our study's success including our use of technology, engagement of a large multilingual team, global partnerships, and framework-based rapid analysis. We hope these techniques may be useful to qualitative researchers conducting studies during the current pandemic, as well as for all pediatric oncology studies including multiple languages or geographically disparate subjects.